Contributions to the study of the flora of the "Frunzeşti" forest, next to Corneşti town, the Republic of Moldova - PÎNZARU, Pavel (Acta et Commentationes Exact and Natural Sciences, 2020)
The article presents the general characteristics of the "Frunzeşti" forest and the outline of the vascular flora made up of 299 species of plants from 186 genera, 51 families. For the first time the species Geranium dissectum L. was registered in the Republic of Moldova. There are 13 rare species protected by law, including 5 species from the Red Book of the Republic of Moldova, 2015 (bold font): Aconitum lasiostomum Rchb, Actaea spicata L., Cephalanthera damasonium (Mill.) Druce, Epipactis helleborine (L.) Crantz, Epipactis purpurata Smith, Lathyrus venetus (Mill.) Wohlf., Lilium martagon L., Luzula campestris (L.) DC., Luzula multiflora (Retz.) Lej., Neottia nidus-avis (L.) Rich., Paris quadrifolia L., Scopolia carniolica Jacq., Staphylea pinnata L. It has been proposed to include the forest "Frunzeşti" (235, 2 ha, plots 49-50) in the scientific reserve "Plaiul Fagului".